The contested meanings of cybersecurity: evidence from post-conflict Colombia. Issue 1 (2nd January 2021) - Chenou, Jean-Marie
ABSTRACT: Cybersecurity is a contested concept. While some definitions focus on technical aspects, other insist on the strategic and geopolitical dimensions. Recently, the definition has included development-related aspects in an increasingly digitalised economy. Instead of cybersecurity, international organisations such as the OECD and private companies now focus on the management of digital risk. While this shift represents an opportunity to include new actors and issues on the political agenda, it does not lead to the de-securitisation of cyberspace, nor to the promotion of cyber peace. This article explores the debates around the definition of cybersecurity with a particular focus on how Colombia became one of the first states to follow the 2015 OECD guidelines on the management of digital risk as part of an effort to join the organisation. It describes how the resulting perspective on cybersecurity evidences a market-centred approach focusing on the development of a digital economy. However, it also discusses why the evolution of cybersecurity policies in Colombia represents a missed opportunity to design a cyber peacebuilding policy in a post-conflict context.